Effect of Bisphosphonates on Bone Health in Adult Renal Transplant Patients: Beyond the First Year Posttransplant—A Systematic Review and Meta-Analysis. Issue 1 (June 2019) - Lip, Alyssa; Warias, Ashley; Shamseddin, M. Khaled; Thomson, Benjamin; Wijeratne, D. Thiwanka
Background: Bone mineral density (BMD) decreases postrenal transplantation. Evidence demonstrating the effects of bisphosphonates on BMD and fracture risk beyond 1-year posttransplant is sparse in existing literature, but remains essential to enhance clinical outcomes in this population. Objective: Our study aimed to systematically review and meta-analyze the current literature on the use of any bisphosphonate in the adult renal transplant population beyond the first year of renal transplant to determine its effect on BMD and fracture incidence. Design: We conducted a systematic review and meta-analysis of primary research literature that included full-text, English-language, original randomized clinical trials (RCTs) and observational studies. Setting: Patient data were primarily captured in an outpatient setting across various studies. Patients: Our population of interest was patients older than 18 years who received deceased/living donor kidney transplantation and any bisphosphonate with a follow-up greater than 12 months posttransplantation. Measurements: The primary outcome was change in BMD from baseline. Secondary outcomes were the incidence of fractures and effects of other confounders on bone health. Methods: We included RCTs and observational studies that satisfied our inclusion criteria. Each study was analyzed for risk of bias and data were extrapolated to analyze for overall statistical significance accounting for heterogeneity of studies. Results: Sixteen studies (N = 1762) were analyzed. The follow-up ranged from 12 to 98 months. There was a nonsignificant improvement in BMD with bisphosphonate treatment persisting into the second and third years posttransplant at the lumbar spine. The calculated standardized mean BMD difference was −0.29 (−0.75 to 0.17), P = .22. Only 5 studies reported a total of 43 new fractures. Prednisone ( P < .01), low body weight ( P < .001), low body mass index ( P < .01), and male gender ( P < .05) correlated with reduced lumbar and femoral BMD. Limitations: Limitations of this review include the use of BMD as a surrogate outcome, the bias of the included studies, and the incomplete reporting data in numerous analyzed studies. Conclusions: We demonstrate no statistically significant benefit of bisphosphonate treatment on BMD beyond the first year postrenal transplantation. Despite heterogeneity of treatment, a differential nonsignificant improvement in lumbar spine BMD was consistent and may be clinically relevant. Trial Registration: PROSPERO CRD42019125593